Maghemite (hematite) core (shell) nanorods via thermolysis of a molecular solid of Fe-complex - Chaudhari, N. S.; Warule, S. S.; Muduli, Subas; Kale, B. B.; Jouen, Samuel; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra B. (Dalton Transactions, 2011)
An Fe-metal complex with 2'-hydroxy chalcone (2'-HC) ligands [Fe(III) (2'-hydroxy chalcone) 3] is synthesized by a chemical route and is subjected to different thermal treatments. Upon thermolysis in air at 450 degrees C for 3 h the complex yields maghemite (gamma-Fe(2)O(3)) nanorods with a thin hematite (alpha-Fe(2)O(3)) shell. X-Ray diffraction (XRD), Mossbauer spectroscopy, diffuse reflectance spectroscopy (UV-DRS), high resolution transmission electron microscopy (HR-TEM), field emission scanning electron microscopy (FE-SEM) and vibrating sample magnetometry (VSM) are used to characterize the samples. The stability of the ligand and the Fe-complex is further examined by using thermogravimmetric/differential thermal analysis (TGA/DTA). We suggest a residual ligand controlled mechanism for the formation of an anisotropic nanostructure in a crumbling molecular solid undergoing ligand decomposition. Since the band gap of iron oxide is in the visible range, we explored the use of our core shell nano-rod sample for photocatalytic activity for H(2) generation by H(2)S splitting under solar light. We observed high photocatalytic activity for hydrogen generation (75 ml h(-1)).

Magnetite/CdTe magnetic-fluorescent composite nanosystem for magnetic separation and bio-imaging - Kale, Anup; Kale, Sonia; Yadav, Prasad; Gholap, Haribhau; Pasricha, Renu; Jog, Jyoti Prakash; Lefez, Benoit; Hannoyer, Beatrice; Shastry, Padma; Ogale, Satishchandra B. (Nanotechnology, 2011)
A new synthesis protocol is described to obtain a CdTe decorated magnetite bifunctional nanosystem via dodecylamine (DDA) as cross linker. High resolution transmission electron microscopy (HRTEM), energy-dispersive x-ray spectroscopy (EDAX), vibrating sample magnetometry (VSM), Fourier transform infrared spectroscopy (FTIR), diffuse reflectance spectroscopy (DRS) and fluorescence microscopy are used to characterize the constitution, size, composition and physical properties of these superparamagnetic-fluorescent nanoparticles. These CdTe decorated magnetite nanoparticles were then functionalized with anti-epidermal growth factor receptor (EGFR) antibody to specifically target cells expressing this receptor. The EGFR is a transmembrane glycoprotein and is expressed on tumor cells from different tissue origins including human leukemic cell line Molt-4 cells. The magnetite-CdTe composite nanosystem is shown to perform excellently for specific selection, magnetic separation and fluorescent detection of EGFR positive Molt-4 cells from a mixed population. Flow cytometry and confocal laser scanning microscopy results show that this composite nanosystem has great potential in antibody functionalized magnetic separation and imaging of cells using cell surface receptor antibody.

MOF derived porous carbon-Fe3O4 nanocomposite as a high performance, recyclable environmental superadsorbent - Banerjee, Abhik; Gokhale, Rohan; Bhatnagar, Sumit; Jog, Jyoti Prakash; Bhardwaj, Monika; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Materials Chemistry, 2012)
A high surface area carbon composite with Fe3O4 nanoparticles is synthesized by pyrolysis of an iron containing Metal Organic Framework (MOF). The composite can be prepared by annealing the MOF at different temperatures (500 degrees C and 600 degrees C), each case exhibiting unique properties in terms of the hydrophobic behaviour and surface area, resulting in specific applicability domains. We highlight the exceptional behaviour of this material as a magnetically separable and recyclable superadsorbent for removal and recovery of environmental pollutants (oil/hydrocarbon and dye/phenol).